Efeito antinociceptivo e anti-inflamatório do carvacrol em modelo experimental de osteoartrite em ratas - ATAIDE, Ana Caroline Santos (2022)
ABSTRACT Osteoarthritis (OA) is a chronic degenerative osteoarticular disease characterized by progressive degradation of joint cartilage, associated with inadequate tissue repair and inflammation. Treatment with standard drugs is quite expensive and associated with adverse effects due to the prolonged use of these drugs, it increases the need to search for new therapeutic options, and among them, chemical compounds extracted from plants are a promising alternative. Among these components, carvacrol stands out, which has numerous biological properties already described in the literature. This work aimed to evaluate the antinociceptive and anti-inflammatory activity of carvacrol in an experimental model of osteoarthritis in rats. To perform this study, 35 rats of the Rattus norvegicus species (Albinus variety), Wistar lineage, adult (60 days old) used up, divided into seven groups, namely: Healthy Group; Sham Group; Negative Control Group: OA induction and without treatment; Carvacrol 20mg group: with OA induction and treated with carvacarol 20 mg/kg, 1x a day; Carvacrol 40mg group: with OA induction and treated with carvacarol 40 mg/kg, 1x a day; Association Group: with OA induction and treated with a combination of carvacrol 10 mg/kg + indomethacin 1.25 mg/kg; Indomethacin Group (Positive Control): animals with OA induction and treated with Indomethacin 2.5 mg/kg, 1x a day. On days 4, 7, 14, 21 and 28 after OA induction and treatment, clinical and behavioral evaluations (motor activity/forced walking, quantification of spontaneous pain and evaluation of mechanical allodynia, and analysis of disability/weight distribution in the hind legs and mechanical hyperalgesia) were performed. In addition, radiological examinations on the 21st day of treatment held up. The animals were treated by gavage and, at the end of the 28-day experimental period, after euthanasia, peripheral blood was collected for hematological and biochemical analysis. The results showed that carvacrol at a dose of 40 mg/kg and its association with indomethacin in the tests carried out had an antinociceptive effect. The pro-inflammatory activity with TNF-α attenuated the production of the TNF-α level in the carvacrol 40 mg/kg and combination groups. In the IL-10 analysis, the indomethacin group, compared with the carvacrol 40 mg/kg groups and the association group, did not show statistical significance, which in this analysis may show similar efficiency to the standard treatment used. In conclusion, the carvacrol 40 mg/kg and association groups showed analgesic and anti-inflammatory activity in the proposed experimental model.